Genetic and biotechnological approaches to preserve food quality against climate change - Carmen Laezza; Silvana Francesca; Amalia Barone; Maria Manuela Rigano (Food and Agricultural Immunology)
In this past decade, the bond between agriculture, food security, and climate change has become increasingly strong. Agriculture is recognized as one of the most endangered systems adversely affected by human activities and environmental issues. In particular, abiotic stress limits the quantity and quality of plant-based food. Heat stress, drought, and salinity impact plants at all different life stages, inducing morphological and physiological changes and provoking a reduction in their nutritional value. Accordingly, low-quality food results in a serious risk for the health of people worldwide. In this scenario, different genetic and biotechnological strategies have been investigated, including the use of New Plant Breeding Techniques (NBTs) and plant cell cultures. In this review, we describe how abiotic stresses alter the property and availability of nutritious food. In addition, we illustrate the advanced techniques that could be employed to address these issues and ameliorate the agricultural practices